Export Competitiveness of Lampung Province Cassava Starch - Nur Syavira Rahmalia Putri; Novi Rosanti; Zainal Abidin (Journal of Food System & Agribusiness, 2022)
This study analyze comparative and competitive advantages export of Lampung Provincecassava starch. The data used secondary time series data for period 2009-2020. The methodused is quantitative descriptive method. Data analyses used revealed comparative advantage(RCA), the trade specialization index (ISP), and the Porter's diamond model. Research wasconducted on March-June 2021. The result showed that Lampung Province cassava starchhas comparative advantage or strong competitiveness with an average value RCA 16,92. TheISP value shows a result of 0,69 or in a growth position and Lampung Province tends to bean exporter of cassava starch. In terms of competitive advantage Lampung Province hasweak competitiveness because the main component do not supported each other.